Intracerebral transplantation for neurological disorders. Lessons from developmental, experimental, and clinical studies - Benchoua, Alexandra; Onteniente, Brigitte (Frontiers in Cellular Neuroscience, 2012)
The use of human pluripotent stem cells (PSCs) for cell therapy faces a number of challenges that are progressively answered by results from clinical trials and experimental research. Among these is the control of differentiation before transplantation and the prediction of cell fate after administration into the human brain, two aspects that condition both the safety and efficacy of the approach. For neurological disorders, this includes two steps: firstly, the identification of the optimal maturation stage for transplantation along the continuum that transforms PSCs into fully differentiated neural cell types, together with the derivation of robust protocols for large-scale production of biological products, and, secondly, the understanding of the effects of environmental cues and their possible interference with transplanted cells commitment. This review will firstly summarize our knowledge on developmental processes that have been applied to achieve robust in vitro differentiation of PSCs into neural progenitors. In a second part, we summarize results from experimental and clinical transplantation studies that help understanding the dialogue that establishes between transplanted cells and their host brain.